The Biological Function, Mechanism, and Clinical Significance of m6A RNA Modifications in Head and Neck Carcinoma: A Systematic Review - Jing, Feng-Yang; Zhou, Li-Ming; Ning, Yu-Jie; Wang, Xiao-Juan; Zhu, You-Ming (Frontiers in Cell and Developmental Biology, 2021)
Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers, yet the molecular mechanisms underlying its onset and development have not yet been fully elucidated. Indeed, an in-depth understanding of the potential molecular mechanisms underlying HNSCC oncogenesis may aid the development of better treatment strategies. Recent epigenetic studies have revealed that the m6A RNA modification plays important roles in HNSCC. In this review, we summarize the role of m6A modification in various types of HNSCC, including thyroid, nasopharyngeal, hypopharyngeal squamous cell, and oral carcinoma. In addition, we discuss the regulatory roles of m6A in immune cells within the tumor microenvironment, as well as the potential molecular mechanisms. Finally, we review the development of potential targets for treating cancer based on the regulatory functions of m6A, with an aim to improving targeted therapies for HNSCC. Together, this review highlights the important roles that m6A modification plays in RNA synthesis, transport, and translation, and demonstrates that the regulation of m6A-related proteins can indirectly affect mRNA and ncRNA function, thus providing a novel strategy for reengineering intrinsic cell activity and developing simpler interventions to treat HNSCC.